MyConvenient travel application / Khairuyanie Ashmier Roslan ... [et al.] - Roslan, Khairuyanie Ashmier; Arkim, Mohamad Akrami; Jomin, Jessyanna; Awang, Nurfaizah; Gatu, Alvin (Faculty of Computer and Mathematical Sciences, 2022)
Nowadays, the population of disabled people has increased, raising awareness about their right to use public services, including those in the tourism industry. Although these disabled people are often overlooked, they are still a part of society. Disabled people typically receive less attention in the tourism industry, thus the MyConvenient Travel application can assist them if they intend to travel and this can contribute to higher satisfaction level. The main objective of this application is to help disabled people to search for places of interest that provides facilities for disabled people hence make the trip easier. This is since most places in our country are not accessible to the disabled. Furthermore, the government should take appropriate action in ensuring the disabled have access to these places without feeling hampered. The second objective is to provides up-to-date, accurate, and dependable accessibility information for tourist attractions. In some ways, this application could be used to assist people with disabilities with their travel itinerary. Finally, this application reduces the social exclusion of people with disabilities in society. With this application, it shows to the people with disabilities that they are not being ignored but appreciated by the society.